PENGARUH KOMPETENSI TERHADAP KINERJA KARYAWAN DI KANTOR KECAMATAN KAWANGKOAN UTARA KABUPATEN MINAHASA - GIROTH, CHRISTINIA; POSUMAH, JOHNNY HANNY; TAMPONGANGOY, DEYSI (JURNAL ADMINISTRASI PUBLIK, 2018)
Abstract: The purpose of this research is to know how big influence of Employee's Competence to EmployeePerformance in District Kawangkoan Utara, based on five competency indicator.This research was conducted in North Kawangkoan Subdistrict with the topics studied concerning theInfluence of Competence on Employee Performance in North Kawangkoan Sub-district which is authorized inexecuting and coordinating the implementation of local government affairs implemented by all regional toolsTo solve the main problem faced in this research method used writer in this research is descriptive analysismethod and simple linear degresi analysis with data collection through Quantitative Data, while the data sourceused is Primary Data obtained directly from the research location through the distribution of questionnaireswith informants related to research problems and secondary data obtained by collecting data through severalliterature, articles, scientific papers, and analysis materials related to this research.The results of this study showed that the influence of competence variables on employee performance in NorthKawangkoan district is 37, 21%. As for the rest of 62, 79% influenced by other factors outside this regressionmodel. This means that together knowledge, skills, self-concept and values, personal characteristics, andmotivation affect the performance of employees in North Kawangkoan Subdistrict. Partially self-concept andvalues have the most dominant influence and motivation has no significant effect on employee performance ofNorth Kawangkoan SubdistrictKeywords: Competence, Performance